Effects of seed size on germination, vigor and yield of corn (Zea mays L.) - Marcos Filho, Julio; Silva, Álvaro Eleutério da; Cicero, Silvio Moure; Gonçalves, Carlos Alberto R. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1977)
The effects of seed size on germination, vigor and yield of corn (Zea mays L.) were studied by means of laboratory tests and a field experiment. The following tests were performed: first count of germination, rapid aging and ammonium chloride test. The effect on yield was determinated by means of a randomized block design field experiment. Analysis and interpretation of results showed that seed size had no influence on germination, vigor and yield.